The advancements in understanding the pathogenesis of ear fullness - Shimin Zong; Wenting Yu; Xuan Yu; Ting Li; Wei Tang; Tianyi Liu; Hongjun Xiao (Journal of Otology)
The sensation of ear fullness is a prevalent symptom encountered in clinical practice at ear clinics. It can manifest in various conditions, including external auditory canal diseases, middle ear diseases, inner ear diseases, as well as non-ear related disorders such as autonomic nervous dysfunction and temporomandibular joint dysfunction. Despite extensive research efforts, the underlying mechanism of ear fullness remains complex and not fully elucidated. Furthermore, the mechanism of ear fullness varies depending on the specific anatomical site and associated disease pathology. In this article, we have conducted a comprehensive literature review to explore the mechanisms underlying ear fullness across different sites of the auditory conduction pathway. By focusing on these lesions and their correlation with ear fullness, we aim to provide an updated understanding on the etiology, diagnosis, and therapy for ear fullness-related diseases.